A case report of an ethanol-related decompensated chronic liver disease with complications - M., Yashfeen; R., Thilakavathi (International Journal of Research in Medical Sciences, 2023)
Decompensated chronic liver disease, is a histopathologically defined condition with a variety of clinical symptoms and complications, some of which are associated with an increased risk of in-hospital mortality. Cirrhosis is predicted to affect 100 (range 25-400) per 100,000 people worldwide, with a male-to-female ratio of one. Patients with ethanol-related cirrhosis have a 5-year death rate ranging from 60-85%. One of the leading causes of cirrhosis is alcoholism. However, it can also be caused by non-alcoholic steatohepatitis (NASH), autoimmune disorders, and viral hepatitis. The decompensated chronic liver disease carries a 9.7 times greater chance of mortality. Cirrhosis is a histologic diagnosis, but a combination of clinical, laboratory, and imaging characteristics can help confirm a cirrhosis diagnosis. For evaluating liver cirrhosis, a liver biopsy continues to be the gold standard. A non-invasive approach to assessing liver cirrhosis is transient elastography (FibroScan). Patients with severe cirrhosis may experience several significant sequelae that complicate their clinical path. These include portal hypertension and related side effects, such as gastroesophageal varices, splenomegaly, ascites, hepatic encephalopathy, spontaneous bacterial peritonitis, hepatorenal syndrome, hepatopulmonary syndrome, and hepatocellular carcinoma. In decompensated chronic liver disease, treatment focuses on underlying liver disease, dietary changes, and long-term medical management to control underlying problems. For patients who do not react to other medications, liver transplantation can be an effective long-term therapy option.